(untitled) (ex æquo, 2023)
Gender perspective in initial training for early childhood education teachers: notes about a research carried out in the degree of early childhood education at the University of Cantabria (Spain) In spite of the favourable legal context in Spain during the frst decades of the 21st century for the gender mainstreaming perspective at all educational levels, reality shows that it has not been addressed adequately. In this paper, we present the results of a research carried out in the 1st course of the Degree in Early Childhood Education at the University of Cantabria (Spain), in order to know students’ opinions on the situation of women and men in society, their perceptions about coeducation programmes, the role school should play in the pursuit of equality and students’ vision about the opportunity for incorporating this subject in their degree programme. The research is based on a survey and a focus group.